2017
DOI: 10.1136/injuryprev-2016-042104
|View full text |Cite
|
Sign up to set email alerts
|

Harmful alcohol use among injured adult patients presenting to a Ghanaian emergency department

Abstract: We performed a nested convenience sample survey of harmful alcohol use among injured patients aged 18 years and older treated in the Komfo Anokye Teaching Hospital (Kumasi, Ghana) emergency department (ED). Data from the Alcohol Use Disorder Identification Test, alcohol breath or saliva tests, patient demographics and injury characteristics were collected from an administered survey and medical chart review. A total of 403 subjects were surveyed, and 107 (27%; 95% CI 22 to 31) reported harmful alcohol use. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…There were only 6 car drivers in this study, and 76% of the injured road users were motorcyclists (Damsere-Derry et al 2018). In another study where 1085 road traffic injury patients were investigated, it was found that 42% of both drivers and pedestrians tested positive for alcohol (Forson et al 2017). In a study from the Ivory Coast they performed blood alcohol testing in the emergency department on 672 patients (Diakite et al 2014).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…There were only 6 car drivers in this study, and 76% of the injured road users were motorcyclists (Damsere-Derry et al 2018). In another study where 1085 road traffic injury patients were investigated, it was found that 42% of both drivers and pedestrians tested positive for alcohol (Forson et al 2017). In a study from the Ivory Coast they performed blood alcohol testing in the emergency department on 672 patients (Diakite et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Our results resemble those from Uganda (Biribawa et al 2019), where the pedestrians had a much higher prevalence of alcohol use than drivers. The one Ghanaian study with an adequate number of car drivers shows a different pattern, with approximately the same prevalence in pedestrians and drivers (Forson et al 2017). In Ivory Coast, drivers also had a higher prevalence among drivers compared to pedestrians (Diakite et al 2014).…”
Section: Prevalence (95% Ci)mentioning
confidence: 99%
“…Alcohol is a nearly globally consumed drug that is widely socially accepted. Given that up to 50% of trauma-related injuries occur under the influence of alcohol, it is critical to consider its interaction with general anesthetics 1 3 . The effects of alcohol are dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is a global contributor to numerous diseases and is associated with a vast number of trauma-related injuries 1 3 . It shows dose dependent stimulative or sedative effects but when consumed in higher quantities central nervous system depressive effects become more pronounced 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, for example, an estimated 70% of countries lack access to vital or civil registration homicide data, which greatly impedes research on the burden of IPVRI and its associated risk factors. 2 To fill this gap, recent research has used hospital-level [17][18][19][20][21][22][23][24][25][26][27][28] or demographic survey [29][30][31][32][33][34] data to better characterise the burden of IPVRI in sub-Saharan Africa. There remains a need for further research on IPVRI, though, as many of these studies have been limited by small sample size, a broad definition of interpersonal violence, lack of focus on risk and protective factors or absence of a control group.…”
Section: Bmj Global Healthmentioning
confidence: 99%